2020
DOI: 10.1111/pan.13856
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics of an intravenous bolus dose of clonidine in children undergoing surgery

Abstract: Background Clonidine is used off‐label in children but only limited pediatric pharmacokinetic data are available for intravenously administered clonidine. Objectives To determine pharmacokinetic parameter estimates of clonidine in healthy children undergoing surgery and to investigate age‐related differences. Furthermore, to investigate possible pharmacokinetic differences of clonidine between this group of children and a cohort with cardiac diseases. Methods In a randomized placebo‐controlled trial (The PREVE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…29 In the present study, when one considers that patients submitted to Treatment 1 received the total amount of 360 mg lidocaine, 30 mg dexamethasone and 75 mcg clonidine; while in Treatment 2 they received the total amount of 200 mg lidocaine, 30 mg dexamethasone and 75 mcg clonidine. However, the time elapsed until each patient was crossed to the following Treatment was always superior to 3 months (3-8 months; minimum-maximum) which would be enough for avoiding any systemic action of lidocaine, 30 dexamethasone, 31 or clonidine. 32 Consequently, the results obtained in the actual study would imply that all analgesia benefit observed in this study was secondary of the central action of each block or RF.…”
Section: Discussionmentioning
confidence: 99%
“…29 In the present study, when one considers that patients submitted to Treatment 1 received the total amount of 360 mg lidocaine, 30 mg dexamethasone and 75 mcg clonidine; while in Treatment 2 they received the total amount of 200 mg lidocaine, 30 mg dexamethasone and 75 mcg clonidine. However, the time elapsed until each patient was crossed to the following Treatment was always superior to 3 months (3-8 months; minimum-maximum) which would be enough for avoiding any systemic action of lidocaine, 30 dexamethasone, 31 or clonidine. 32 Consequently, the results obtained in the actual study would imply that all analgesia benefit observed in this study was secondary of the central action of each block or RF.…”
Section: Discussionmentioning
confidence: 99%